AN ANALYSIS OF SLANG WORD USED IN THE LAST RESCUE MOVIE - Sutrisna, I Wayan Ebik Arya; Suastini, Ni Wayan; Aryaningsih, Ni Nyoman Deni (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2023)
This research was made to find out and examine the meaning of slang, the types of slang and the types of meaning contained in the film that is used as data, the film entitled The Last Rescue, this film tells the journey of a Private James Lewis and his friends surviving attacks and pursuit of the Nazis. This study uses qualitative methods to collect data from the formulation of the problem as much as possible so that it can be researched, describes and explains the problems found. In this data research is carried out by taking from the script, watching the film used as research and applying it to several stories used in the research. This research is similar to the theory of slang words proposed by Kipfer and Chapman (2007) with the title of the book "Dictionary of American Slang" which explains and classifies slang into two parts, namely primary slang and secondary slang and the theory of types of meaning proposed by Leech (1981). "Semantic the Study of Meaning" which explains and classifies into seven meanings, namely, conceptual meaning, connotative meaning, collocative meaning, social meaning, affective meaning, reflective meaning and thematic meaning, one of these seven meanings will be classified into a slang words in the data.